أثر بعض المتغيرات الوظيفية في سلوك القيادات الإدارية:(دراسة ميدانية في جامعة الموصل) - حيدر خضر سليمان (PROSPECTIVE RESEARCHES, 2023)
This research is intended to shed light on the space of care the deans of the colleges and heads of scientific departments show towards work and production (teaching and managing processes) and how much care they show towards their employees, i.e building good relationship with their officials and students, in addition to a number of functional variables such as positions, academic titles, and serving periods). The study sample comprises (100) university leaders, who have been randomly chosen from Mosul University. The researcher has followed the descriptive method which properly suits this study and questionnaire for collecting data. These data have been manipulated using one way variant analysis. Consequently the analysis shown that the deans and heads have a tendency towards care to work and human relationships. Besides, there are statistical differences in the care towards work and human relationships according to the variables of position and academic titles. Whereas there are no such differences towards work and human relationships in the matter of years of experience. On the light of these results, the researcher presents a number of recommendations.